2020
DOI: 10.3390/min10010059
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Thermoelasticity of Liquid Iron-Nickel-Light Element Alloys

Abstract: The earth’s core is thought to be composed of Fe-Ni alloy including substantially large amounts of light elements. Although oxygen, silicon, carbon, nitrogen, sulfur, and hydrogen have been proposed as candidates for the light elements, little is known about the amount and the species so far, primarily because of the difficulties in measurements of liquid properties under the outer core pressure and temperature condition. Here, we carry out massive ab initio computations of liquid Fe-Ni-light element alloys wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…The effect of oxygen on Ks is more pronounced than on ρ, resulting in a reduction of Vp (this study; Komabayashi 2014) a positive effect. Another recent first-principle calculations by Ichikawa and Tsuchiya (2020) predicted similar trends to those in Badro et al (2014) (Fig. 10).…”
Section: Liquids In the System Fe-si-o And Silicon And Oxygen In The supporting
confidence: 77%
See 3 more Smart Citations
“…The effect of oxygen on Ks is more pronounced than on ρ, resulting in a reduction of Vp (this study; Komabayashi 2014) a positive effect. Another recent first-principle calculations by Ichikawa and Tsuchiya (2020) predicted similar trends to those in Badro et al (2014) (Fig. 10).…”
Section: Liquids In the System Fe-si-o And Silicon And Oxygen In The supporting
confidence: 77%
“…Similarly the effects of silicon on the bulk modulus are in contrast between the experiment-based (this study) and theory-based models (Badro et al 2014;Ichikawa and Tsuchiya 2020) although all the papers show positive effects on the Vp (Fig. 10a).…”
Section: Liquids In the System Fe-si-o And Silicon And Oxygen In The mentioning
confidence: 61%
See 2 more Smart Citations
“…[ 25 ] In addition, Ichikawa and Tsuchiya evaluated the thermoelasticity of liquid FeNiLE alloys using ab initio MD simulations. [ 26 ] It was found that Si and S have a greater effect on the density of liquid iron than O and H.…”
Section: Introductionmentioning
confidence: 99%